Receptive range analysis of a mouse odorant receptor subfamily - Li, Jingyi (J Neurochem, 2015)
Mammals deploy a large array of odorant receptors (ORs) to detect and distinguish a vast number of odorant molecules. ORs vary widely in the type of odorant structures recognized and in the breadth of molecular receptive range (MRR), with some ORs recognizing a small group of closely related molecules and other ORs recognizing a wide range of structures. While closely related ORs have been shown to have similar MRRs, the functional relationships among less closely related ORs are unclear. We screened a small group of ORs with a diverse odorant panel to identify a new odorant-OR pairing (unsaturated aldehydes and MOR263-3). We then extensively screened MOR263-3 and a series of additional MORs related to MOR263-3 in various ways. MORs related by phylogenetic analysis (several other members of the MOR263 subfamily) had MRRs that overlapped with the MRR of MOR263-3, even with amino acid identity as low as 48% (MOR263-2). MOR171-17, predicted to be functionally related to MOR263-3 by an alternative bioinformatic analysis, but with only 39% amino acid identity, had a distinct odorant specificity. Our results support the use of phylogenetic analysis to predict functional relationships among ORs with relatively low amino acid identity.